Deploying high-frequency market data to estimate the cost of recommended diets: Recent trends in Rwanda - Manners, Rhys; Warner, James; Schneider, Kate; Matsiko, Eric; Vasanthakaalam, Hilda; Benimana, Gilberthe; Spielman, David J. (International Food Policy Research Institute, 2025)
This study estimates the cost and affordability of recommended diets in Rwanda from April 2019 to December 2024 using high-frequency market price data. By deploying standardised methods for healthy diet costs to eSoko data (www.esoko.gov.rw), and local food based dietary guidelines, we calculate the monthly cost of recommended diets at the district level. Key findings reveal significant dietary cost fluctuations, with nominal costs increasing 67% between June 2022 and October 2023, coinciding directly with Russia’s invasion of Ukraine. The research also identifies affordability challenges; by mid-2023, and again in late 2024, where up to 70% of wage earners could not afford a recommended diet. Spatial variations were also evident, with diet costs differing between rural and urban areas, and across districts bordering different countries, with the highest dietary costs observed along the Democratic Republic of Congo border and the least expensive along the border of Tanzania. Utilizing Rwanda's eSoko data platform, the study demonstrates the value of high-frequency, spatially explicit data for understanding food system dynamics. The findings call for policy actions to consider dietary affordability, particularly for low-income groups, and suggest that Rwanda's data collection approach could serve as a benchmark for other countries.